ANALISA PENERAPAN PRINSIP- PRINSIP GOOD CORPORATE GOVERNANCE DAN PENGENDALIAN INTERNAL - Iskandar, Bintang Kusnardani; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The implementation of Good Corporate Governance (GCG) is the concept which emphasizes the obligations and the rights which are owned by the elements of Cooperative GCG. The elements of cooperative GCG i.e.: member, caretaker, supervisor, PPL, group PJ, internal audit group and management staffs. Problem about how the whole elements of GCG carry out their obligations and rights in accordance with the portion of each position is adjusted to the existing GCG principles will be discussed in this research. The GCG principles are transparency, accountability, autonomy, responsibility, and fairness. This research will explain about how the main supporting element of GCG in the cooperative in the form of internal control is conducted. It has been obtained from the result of the analysis that the caretakers of Kopwan SBW has conducted the implementation of GCG successfully and the supervisor has monitored the course of the implementation of GCG principles has been done by the whole elements of GCG cooperative. The caretakers has carried out all efforts to maintain the values of GCG principles by the internal control system which is supported by all elements of GCG cooperative with the implementation of Reward and Punishment system as one of motivation instruments of GCG elements in running the regulations..Keywords: Good Corporate Governance, Cooperative, Cooperative Stakeholder